Closed‐incision negative pressure therapy to reduce groin wound infections in vascular surgery: a randomised controlled trial. Issue 3 (12th March 2018) - Engelhardt, Michael; Rashad, Norah A; Willy, Christian; Müller, Christian; Bauer, Christian; Debus, Sebastian; Beck, Tino
Abstract: Groin wound infections pose a major problem in vascular surgery. Closed‐incision negative pressure therapy (ciNPT) was especially designed for the management of incisions at risk of surgical site infections. The aim of this study was to investigate whether ciNPT is able to reduce the incidence of wound infections after vascular surgery. Data on 132 consecutive patients, scheduled for vascular surgery with a longitudinal femoral cutdown, were collected prospectively. All patients were randomised either to the ciNPT group ( n = 64) or the control group ( n = 68) with conventional dressing. In the ciNPT group, the foam dressing was applied intraoperatively and removed after 5 days. The control group received an absorbent dressing. All wounds were evaluated after 5 and 42 days. Infections were graded according the Szilagyi classification (I–III°). There were no significant differences between both groups considering patient characteristics. Indications for surgery were peripheral arterial disease in 95% (125/132) and aneurysm in 5% (7/132). The overall infection rates were 14% (9/64) in the ciNPT group and 28% (19/68) in the control group ( P = 0·055). Early infections were observed in 6% (4/64) of the ciNPT group and 15% (10/68) of the control group ( P = 0·125). ciNPT did not reduce infection rates associated with different risk factors for infection. While the experiences with the ciNPT device were encouraging, the study fails to provide evidence of the efficacy of the device to reduce groin wound infections after vascular surgery. It illustrates far more that larger multicentre studies are required and appear promising to provide further evidence for the use of ciNPT.